터널화재시 콘크리트 라이닝의 폭렬 및 화재손상에 관한 실험적 연구 - 김흥열(Kim, Heung-Youl); 김형준(Kim, Hyung-Jun); 조경숙(Cho, Kyung-Suk); 이재승(Lee, Jae-Sung); 권기혁(Kwan, Ki-Hyuk) (한국화재소방학회 논문지, 2009)
In tunnel, though the frequency of fire occurrence is relatively lower than other structures, the characteristics of sealed space tends to cause the temperature to rapidly rise to more than $1000^{°}C$ within 5minutes after fire, which might eventually lead to a large fire that usually results in a loss of lives and the damage to the properties, not to mention a huge cost necessary for repair and maintenance after fire. We have developed various conditions of the heating furnace and the method to install a thermo couple within the furnace based on EFNARC and KS F 2257-1. Referring to tunnel fire scenarios, it clarified the heat transfer characteristics of concrete PC panel lining depending on fire intensity (ISO, $1^{°}C$/SEC, MHC, RWS), and to identify the range of thermal damage, the evaluation was carried out using ITA standard. As a result, 30mm under ISO fire condition, 20mm under $1^{°}C$/SEC, 100mm under MHC and 50mm under RWS were measured. And when it comes to spalling, 30mm was measured under RWS and MHC. 터널의 경우 타구조물에 비해 화재빈도가 상대적으로 높지는 않으나, 밀폐된 공간이라는 특성상 5분 이내 $1000^{°}C$ 이상으로 급격한 온도상승이 발생할 수 있으므로, 화재발생시 대형 인명피해 및 화재 후 막대한 보수 보강비용이 파생된다. 이러한 터널화재로 인한 구조적 손상을 규명하기 위해, KS F 2257-1과 EFNARC 규정에 부합하고 터널 콘크리트 라이닝의 화재손상평가가 가능한 가열로를 개발하였다. 개발된 가열로를 실증실험에 사용하여 터널화재 시나리오(ISO, $1^{°}C$/SEC, MHC, RWS)에서의 콘크리트 PC패널라이닝의 폭렬특성과 화재손상범위를 ITA기준을 적용하여 평가하였다. 실증실험결과 ISO 화재조건에서는 30mm, $1^{°}C$/SEC에서는 20mm, MHC에서는 100mm, RWS에서는 50mm로 화재손상범위가 평가되었으며, 폭렬깊이는 RWS와 MHC 화재조건에서 30mm가 발생하는 것으로 나타났다.